Analysis and Review of MSME Financial Reports at Edo Cell - Ach. Randy Arief Pratama Purnomo; Sintia Anisa Putri; Mohammad Solihin; Rovatul Kholidah; Muhammad Imam Safi'i; Dhea Andrian (Medikun Publisher, 2024)
Financial reports can be a reference for knowing the company's financial performance in one period. Regular presentation of financial reports can show how the business conditions are developing. And business owners can evaluate company performance. The aim of this research is to analyze the preparation of MSME financial reports, whether SAK EMKM is implemented, and to analyze the advantages and disadvantages of recording financial reports on Edo Cellular. The research method used is a descriptive method, namely analyzing financial reports prepared by Edo Cellular. The results of the research show that in preparing its financial reports, Edo Cellular does not use an accounting application so reports on cash receipts and disbursements are prepared manually and the implementation of SAK EMKM on Edo Cellular has not been implemented in preparing its financial reports, considering that there is no competent workforce and the absence of the government's role. which collaborates with MSME players to provide knowledge and apply applicable accounting standards.